IMPROVING STUDENTS’ IMPROMPTU PUBLIC ENGLISH SPEAKING ABILITY THROUGH BRAINSTORMING METHOD - Syamsuddin, Suci Ramadhana; Baa, Sultan; Aeni, Nur (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study aims to find out whether the brainstorming method can improve students' impromptu public speaking ability. The researcher applied pre-experimental method and to achieve the research objectives, data collection was conducted through pre-test and post-test. The population of this study is all of the second grade of SMAN 16 Makassar students and the sample of this study consisted of 35 students of class 11 MIPA 6 at SMA 16 Makassar with random sampling technique. The results of the pre-test and post-test of impromptu public speaking after being analyzed with the significant test formula showed a T-Test value that was greater than the T-Table value so H0 was accepted, and after being analyzed with the N-Gain value the results showed that the improvement that occurred in the speaking ability of the sample group was low. Keywords- Impromptu public speaking, brainstorming method